Fractionation and Liquid Immiscibility in an Anorthositic Pluton of the Nain Complex, Labrador - WIEBE, R. A. (Journal of Petrology, 1979)
Fine-grained anorthositic dikes are associated with a massive leuconorite pluton (Cl = 15) which is exposed over an area of about 200 km2. Internally, the pluton shows little compositional variation; average plagioclase composition ranges from An 52 to An 48 . The dikes are nearly uniform in composition and similar to the estimated bulk composition of the pluton (55 per cent SiO 2 ). They therefore appear to represent the parental magma of the leuconorite pluton. A small body of granite (10 km2) was emplaced within and prior to the complete solidification of the leuconorite. The granitic intrusion caused local deformation of the leuconorite and filter-pressing of its late stage interstitial liquids. These liquids occur in the younger hydrous granite as very finegrained, chilled pillows of nearly anhydrous Fe-rich diorite and granite. Most of the pillows are diorites with approximately 55 per cent SiO 2 . On oxide plots these lie approximately on a plagioclase control line passing through the composition of the leuconorite dikes. The entire group of chilled pillows ranges in composition from 45 to 71 per cent SiO 2 with a gap between 57 and 63 per cent SiO 2 . On oxide plots they produce a smooth trend which is oblique to and truncates the plagioclase control line. Variation in the pillows can best be explained by late-stage liquid immiscibility. Fractionation in the interstitial magma was controlled early by crystallization of plagioclase and later by plagioclase plus pyroxene. Very late stage differentiation was controlled mainly by liquid immiscibility and produced FeO- and SiO 2 -rich liquids.